THE INFORMATION SYSTEM AT INTEGRATED TRANSPORTATION SYSTEM (Perner's Contacts, 2009)
The contribution describes ways of supllying good-class information for passengers in integrated transportation system. It defines the standard of technical operation and maintenance information system.
Keywords: passenger; information; system